2020
DOI: 10.1101/2020.03.14.979047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased severity of closed head injury or repetitive subconcussive head impacts enhances post-traumatic headache-like behaviors in a rat model

Abstract: Introduction: Posttraumatic headache (PTH) is one of the most common, debilitating and difficult symptoms to manage after a traumatic head injury. The development of novel therapeutic approaches is nevertheless hampered by the paucity of preclinical models and poor understanding of the mechanisms underlying PTH. To address these shortcomings, we previously characterized the development of PTH-like pain behaviors in rats subjected to a single mild closed head injury using a 250 g weight drop. Here, we conducted… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Finally, neurogenic inflammation after mTBI, including the release of calcitonin gene-related peptide (CGRP), might contribute to the initial development of PTH as well as the development of trigeminal and extratrigeminal sensitization, which facilitate PTH persistence (42,43). Preclinical studies that block CGRP have demonstrated benefits for reducing post-TBI pain behaviors, early sensitization, late latent sensitization, and photophobia (44)(45)(46). Preclinical and human studies suggest that CGRP might play more of a role early after TBI and PTH onset, with a diminished role after PTH has become persistent (45,47).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Finally, neurogenic inflammation after mTBI, including the release of calcitonin gene-related peptide (CGRP), might contribute to the initial development of PTH as well as the development of trigeminal and extratrigeminal sensitization, which facilitate PTH persistence (42,43). Preclinical studies that block CGRP have demonstrated benefits for reducing post-TBI pain behaviors, early sensitization, late latent sensitization, and photophobia (44)(45)(46). Preclinical and human studies suggest that CGRP might play more of a role early after TBI and PTH onset, with a diminished role after PTH has become persistent (45,47).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Understanding the mechanism of injury and the tolerance within humans in regard to repetitive subconcussive injuries is vital in developing diagnosis and treatment models. A relationship between repetitive subconcussive injuries and the resulting insidious behavioral and pathological outcomes has yet to be defined in a study that translates to human physiology and subconcussive biomechanical characteristics [115][116][117][118]. Much of the human studies literature is subject to significant variability, particularly in frequency and magnitude of subconcussive impacts.…”
Section: Discussionmentioning
confidence: 99%